Analisis Perkembangan Kurikulum dalam SIM di SMA Muhammadiyah 9 Surabaya - Cahyaningrum, Salsabila Dwi; Jannah, Distya Iftaqul; Arif, Achmad Nur (ARZUSIN, 2023)
This research aims to analyze the development of the SIM curriculum at SMA Muhammadiyah 9 Surabaya. The research method used is qualitative. This type of research data uses data collection techniques such as interviews with subjects required in the research as well as documentation of school data required in the research. The results of the research show that the SIM at SMA Muhammadiyah 9 Surabaya is developing its curriculum using E-KOSP. This system requires updating teaching modules and syllabi. Although there are challenges in curriculum adaptation, this system provides benefits in administrative efficiency. However, security concerns and document collection before the first upload are important for accreditation. Therefore, SMA Muhammadiyah 9 Surabaya needs to strengthen security procedures and document control in using E-KOSP. By improving security systems, schools can ensure that important data and information in their curriculum is well protected. And SMA Muhammadiyah 9 Surabaya must also monitor and evaluate the impact of using this system on the quality of education and learning in their school, and try to continue to improve the learning process based on the results of this evaluation. Thus, the use of E-KOSP can provide greater benefits for the development of education in this school.